Actively produced high-energy electron bursts within the magnetosphere: the APEX project - L. Přech; L. Přech; L. Přech; Z. Nĕmeček; J. Šafránková; A. Omar (Annales Geophysicae, 2002)
The APEX project (Active Plasma Experiment) has been launched into a polar orbit in December 1991 and consists of two satellites (IK-25 and MAGION-3), with a distance between them from 200 km to 10 000 km. The mission used intensive electron beam emission, complemented by a low-energy Xenon plasma generator during the electron beam injection, for the study of dynamic processes in the magnetosphere and upper ionosphere.  The paper deals with short, intensive bursts of field-aligned electrons observed during the APEX mission on board the MAGION-3 satellite. These events are located pre-dominantly at the middle geomagnetic latitudes in the day-side magnetosphere. The time-energy structure of these electron bursts is similar to the inverted-V one, but the pitch-angle width is less than 10°. Electrons with an energy up to 700 keV are often observed during the events. We analyze the observed events, discuss the possible mechanisms of the particle spreading, and the role of the main satellite’s activity as a possible source of these events. Key words. Ionosphere (particle acceleration; particle precipitation) – Space plasma physics (active perturbation experiments)